2017
DOI: 10.17116/terarkh201789553-59
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity venous diseases in primary knee osteoarthritis

Abstract: The 40-60-year-old patients with knee OA more commonly develop symptoms of chronic venous insufficiency than their healthy peers. Although obesity is a risk factor for both diseases, there is an independent association between knee OA and lower extremity VVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Patients with varicose veins in the lower limbs are mostly middle-aged and older women, similar to those with knee osteoarthritis. Patients with knee osteoarthritis have significantly higher prevalence of varicose veins in the lower limbs (43% vs. 22%; p=0.015), 5) and a relatively large number of patients with varicose veins of the lower limbs are believed to have knee osteoarthritis. 6) Obesity is a risk factor for both.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with varicose veins in the lower limbs are mostly middle-aged and older women, similar to those with knee osteoarthritis. Patients with knee osteoarthritis have significantly higher prevalence of varicose veins in the lower limbs (43% vs. 22%; p=0.015), 5) and a relatively large number of patients with varicose veins of the lower limbs are believed to have knee osteoarthritis. 6) Obesity is a risk factor for both.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients with knee OA are reported to develop symptoms of chronic VI more common than their healthy peers. [6] However, VI and OA share common risk factors and the risk of these diseases increases with age. [13] Our results showed that the difference in the frequency of VI between the groups was not remained after the age adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies assessing the contribution of circulatory disturbances in the pathophysiology of OA; however, the number of studies investigating the relationship between peripheral VI and OA is limited. [6] In the present study, we aimed to investigate whether there is a relationship between knee OA and VI.…”
mentioning
confidence: 98%
“…Согласно обобщенным данным эпидемиологических исследований, в разных странах оно отмечается у 35-60% трудоспособного населения [21], являясь одним из О р и г и н а л ь н ы е и с с л е д о в а н и я основных и наиболее распространенных ФР развития ВТЭО. В литературе мы не нашли сообщений об увеличении риска развития варикозного расширения вен нижних конечностей у пациентов с РА, однако имеются данные об увеличении частоты варикозной болезни нижних конечностей у пациентов с остеоартритом [22]. Вторым по значимости ФР ВТЭО была высокая активность РА.…”
Section: Discussionunclassified